Science, Literature, and Film in the Hispanic World
XIV, 250 p.
Keywords: Driven by such diverse advances as the Human Genome Project and the explosion of the World Wide Web, and also by the threat of human-inspired disasters such as global warming, the field of science and literature studies is currently undergoing an unprecedented expansion. The relations between science and literature have been and continue to be central to understanding Hispanic civilization and culture. In spite of this, Science, Literature, and Film in the Spanish-Speaking World is the first and only book to treat this new and dynamic field from an Hispanic perspective. This unique volume opens the door to an entirely new focus in the study of Hispanic literature and culture.